ALN Teaching as Routine Faculty Workload - Hislop, Gregory; Atwood, Michael (Online Learning, 2000)
If the current growth in online education continues, teaching online will become part of routine faculty workload at many traditional, research-oriented universities. This is already occurring within some faculties, and this paper focuses on one of those cases. The paper describes faculty issues related to a completely online graduate degree in Information Systems at Drexel University. Following a brief overview, the paper presents results of a survey of the faculty affected by this degree. The survey addresses faculty support for the degree, and for the prospect of online teaching as a significant, permanent part of the work of the college.